Gestão da diversidade no Brasil: apresentação de um modelo brasileiro - Saji, Genilda Sandra Madeira (2005)
This work presents the concepts of diversity and its management, gotten in foreign and national literature on the subject; it presents a Brazilian scene in the treatment of the subject and investigates its application in Brazilian company of national capital through a case study. As result, this work identify a possible Brazilian model of management of the diversity and presents its restrictions.